EFFECT OF SURFACE MODIFICATION ON TENSILE PROPERTIES OF SANSEVIERIA TRIFASCIATA FIBER-REINFORCED POLYLACTIC ACID (PLA) COMPOSITE FILAMENTS - Ansari Putri, Salsabila
The criteria for bone implant materials include biodegradability, biocompatibility, mechanical properties close to bone, and cost-effective with customizable processing. One material that meets these criteria is Polylactic Acid (PLA) reinforced with natural fibers using Fused Deposition Modeling (FDM) method. Sansevieria trifasciata natural fibers can be used due to their high tensile properties and availability in Indonesia. However, their strength is lower than pure PLA due to poor interfacial bonding. Other research has achieved surface modification of the fibers to enhance the interface. Therefore, this study aims to investigate the effects of Sansevieria fiber surface modification on its tensile properties. Sansevieria fiber surfaces were modified by alkali, bleaching, and ultrasonication, followed by extrusion with PLA. Lignocellulosic content tested using Chesson-Datta. Surface morphology of fibers, fiber diameter, and filament fractures observed using scanning electron microscope. Fiber density was determined through density testing. Fiber and filament tensile properties obtained from tensile tests. Filament morphology observed using an optical microscope. Filament viscosity determined through melt flow rate testing while filament functional groups characterized using Fourier-transform infrared spectroscopy. PLA/Sansevieria fiber composite filaments were successfully produced through extrusion process. Various modifications of Sansevieria fibers, including alkali, combination of alkali and bleaching, and combination of alkali, bleaching, and ultrasonication increased cellulose percentage. Combination of alkali treatment, bleaching, and ultrasonication on PLA/Sansevieria fiber composite filaments with a 1.5% fiber volume fraction increased stiffness by 30% compared to pure PLA filaments. However, their strength still remains lower than pure PLA due to suboptimal fiber adhesion, fiber cutting, and interfacial bonding.